MicroRNA-582-5p inhibits the progression of gastric cancer cells and their resistance to oxaliplatin by suppressing ATG7 expression - Chang, Yu; Hao, Yaqin; Su, Yani; Guo, Jin; Liu, Yu; Sun, Ruixue; Feng, Bei; Ma, Junwei; Hu, Yunfeng (Frontiers in Oncology, 2024)
BackgroundGastric cancer (GC) is one of the most common malignant tumors of the digestive tract worldwide. Both environmental and genetic factors contribute to the occurrence and development of GC. Surgery and chemotherapy are the main treatment modalities for gastric cancer; however, some patients show insensitivity to chemotherapeutic agents. Chemotherapy resistance is one of the primary reasons for poor treatment outcomes and the high likelihood of recurrence and metastasis in gastric cancer patients. Numerous studies have confirmed a correlation between the dysregulation of microRNA expression and the development of various malignant tumors, as well as their resistance to chemotherapeutic agents. However, the role of microRNA-582-3p in gastric cancer cells and its mechanism in the resistance of gastric cancer cells to oxaliplatin have not been studied.MethodsWe first used q-PCR, CCK8, transwell, and scratch assays to validate the expression of microRNA-582-3p in gastric cancer tissues and cells, while also analyzing the relationship between its expression levels and the clinical pathological data of patients. Additionally, we further confirmed the impact of microRNA-582-3p on gastric cancer cell progression and oxaliplatin resistance through knockdown and overexpression experiments. Subsequently, to explore the specific mechanisms of microRNA-582-3p in gastric cancer, we verified the downstream target of microRNA-582-3p, ATG7, using dual-luciferase reporter assays and examined the effect of ATG7 on gastric cancer cell functions. Moreover, we conducted rescue experiments to further validate the interaction between microRNA-582-3p and ATG7.ResultsOur experimental results confirmed that microRNA-582-3p is lowly expressed in gastric cancer tissues and cells, and the expression level of miR-582-5p is correlated with the T stage of patients, while showing no correlation with the patients' gender, age, tumor size, degree of differentiation, or N stage. Additionally, we found that microRNA-582-3p functions as a tumor suppressor in gastric cancer cells, as its overexpression inhibits the biological functions of gastric cancer cells and increases their sensitivity to oxaliplatin. Furthermore, we identified binding sites between microRNA-582-3p and the autophagy-related gene ATG7, observing that knockdown of microRNA-582-3p increases ATG7 expression, while its overexpression reduces ATG7 levels. Moreover, ATG7 is overexpressed in gastric cancer cells; knockdown of ATG7 inhibits the biological functions of gastric cancer cells and increases their sensitivity to oxaliplatin, whereas overexpression of ATG7 reverses the inhibitory effect of miR-582-5p on gastric cancer.ConclusionOur study confirms that microRNA-582-3p acts as a tumor suppressor in gastric cancer cells, and its role may be mediated through the regulation of ATG7 expression levels. MicroRNA-582-3p may serve as a potential target for gastric cancer treatment and a predictive biomarker.